Generation of Col2a1-EGFP iPS Cells for Monitoring Chondrogenic Differentiation - Saito, Taku (Public Library of Science, 2013)
Induced pluripotent stem cells (iPSC) are a promising cell source for cartilage regenerative medicine; however, the methods for chondrocyte induction from iPSC are currently developing and not yet sufficient for clinical application. Here, we report the establishment of a fluorescent indicator system for monitoring chondrogenic differentiation from iPSC to simplify screening for effective factors that induce chondrocytes from iPSC. We generated iPSC from embryonic fibroblasts of Col2a1-EGFP transgenic mice by retroviral transduction of Oct4, Sox2, Klf4, and c-Myc. Among the 30 clones of Col2a1-EGFP iPSC we established, two clones showed high expression levels of embryonic stem cell (ESC) marker genes, similar to control ESC. A teratoma formation assay showed that the two clones were pluripotent and differentiated into cell types from all three germ layers. The fluorescent signal was observed during chondrogenic differentiation of the two clones concomitant with the increase in chondrocyte marker expression. In conclusion, Col2a1-EGFP iPSC are useful for monitoring chondrogenic differentiation and will contribute to research in cartilage regenerative medicine.